Islamic State of Afghanistan : Report on Recent Economic Developments and Prospects, and the Role of the Fund in the Reconstruction Process. (IMF Staff Country Reports; Country Report ;, 2002)
This report examines the recent economic developments and prospects, and the role of the IMF in the reconstruction process for the Islamic State of Afghanistan. Since January 2002, the IMF staff has been heavily involved in assisting the Afghan authorities rebuild key economic institutions and implement macroeconomic policies. The Monetary and Exchange Affairs Department, Fiscal Affairs Department, and Statistics Department have started substantial technical assistance programs. Critical areas of technical assistance are the rebuilding of the payments system, the introduction of a new currency, central bank modernization, expenditure management, and revenue mobilization.